Inflation Risk and the Finance-Growth Nexus - Corhay, Alexandre; Tong, Jincheng (Review of Economic Studies, 2025)
Abstract When firms finance using long-term nominal debt issued by financial intermediaries, changes in expected inflation lead to a wealth transfer across sectors. Higher expected inflation decreases firms’ real liabilities and default risk, which helps reduce debt overhang. However, it hurts intermediaries’ real assets, leading to a contraction in credit supply. We theoretically demonstrate that intermediary financing conditions play a key role in the transmission of nominal shocks, influencing the premium investors require for bearing inflation risk. We provide empirical evidence supporting our novel inflation transmission mechanism and connect our findings to the banking stress of 2023. We also show that Taylor rules responding to both financial and real variables can help stabilise our economy.